Use of ICT Based Services and Its Impact on Users in Some Selected Engineering College Libraries in Haryana: An investigation into the utilization and impact of ICT-based services in engineering college libraries in Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The paper describes the current situation of libraries in ICT environment in Haryana state. Various services provided by libraries with support of Information Communication Technologies to their users have been observed and discussed with the library professionals and their users. The result of the study revealed that the ICT based resource used by the largest percent of users was the e resources.